Design of an Over Current Relay (OCR) System on a Distribution Network Using a Raspberry Pi - Prasetyo, Yuli; Triyono, Budi; Prakoso, Dimas Nur; Kusumo Haryo, R. Jasa (Geuthèë Institute, 2023)
Disturbances in the electrical installation system will be detrimental to electricity users because it can cause power outages. Therefore we need a protection system that can overcome disturbances such as the use of Over Current Relay (OCR). With OCR can overcome interference quickly and can prevent equipment damage. OCR interference occurs if the current read on sensor 1 is more than 10.5 A, then relay 1 will work after a disturbance of 5 seconds. The indicator light on the PLN side will be red. Meanwhile, if the current at sensor 2 is more than 10 A, then relay 2 will work after a disturbance for 5 seconds. The indicator light on the customer side will be red. Short circuit disturbance occurs if the current read on sensor 1 is more than 20.5 A, then relay 1 will work after an interruption of 2 seconds. The indicator light on the PLN side will be red. Meanwhile, if the current on sensor 2 is more than 20 A, then relay 2 will work after a disturbance for 2 seconds. The indicator light on the customer side will be red.